2021
DOI: 10.3389/fcell.2021.763864
|View full text |Cite
|
Sign up to set email alerts
|

Curdione and Schisandrin C Synergistically Reverse Hepatic Fibrosis via Modulating the TGF-β Pathway and Inhibiting Oxidative Stress

Abstract: Hepatic fibrosis is the final pathway of several chronic liver diseases, which is characterized by the accumulation of extracellular matrix due to chronic hepatocyte damage. Activation of hepatic stellate cells and oxidative stress (OS) play an important role in mediating liver damage and initiating hepatic fibrosis. Hence, hepatic fibrosis can be reversed by inhibiting multiple channels such as oxidative stress, liver cell damage, or activation of hepatic stellate cells. Liuwei Wuling Tablets is a traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…showed that Sch C and the combination of both with Curdione had the effect of reversing liver fibrosis in mice. [57] It is found that Sch C inhibited LPS-induced inflammatory responses in mouse macrophages (Raw 264.7 cells). The inhibitory effect is presumed to be caused by blocking the phosphorylation of p38 mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase 1 and 2 (ERK 1/2), and c-Jun N-terminal kinase (JNK).…”
Section: Hdpcs 10 μMmentioning
confidence: 98%
See 1 more Smart Citation
“…showed that Sch C and the combination of both with Curdione had the effect of reversing liver fibrosis in mice. [57] It is found that Sch C inhibited LPS-induced inflammatory responses in mouse macrophages (Raw 264.7 cells). The inhibitory effect is presumed to be caused by blocking the phosphorylation of p38 mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase 1 and 2 (ERK 1/2), and c-Jun N-terminal kinase (JNK).…”
Section: Hdpcs 10 μMmentioning
confidence: 98%
“…It was shown that Sch C significantly inhibited oxidative stress while suppressing hepatic stellate cell activation and preventing hepatocyte injury by targeting the TGF‐ β 1/Smads signaling pathway. Further, in vivo, experiments showed that Sch C and the combination of both with Curdione had the effect of reversing liver fibrosis in mice [57] …”
Section: Bioactivitymentioning
confidence: 99%
“…Brevilin A [270] Curdione [271] Limonin [272] Piperlongumine, [273] Conophylline [274] Apigenin [224] Salvianolic acid B [216] Taxifolin [275] Paeonol [252] Pterostilbene [276] Sesamol [277] Chelerythrine [278] Physalin D [231] Methoxyeugenol [226] Apigenin [227] Dihydromyricetin (DHM)…”
Section: Structural Formula Mechanism Of Action Referencesmentioning
confidence: 99%
“…Apart from the above-mentioned natural products targeting HSC, natural products involved in the following related mechanisms: (1) Intervening in the TGFβ/Smad signaling pathway. The natural products involved are: Tanshinone IIA [225] , Protocatechuic acid [265] , Byakangelicin [266] , Quercetin [267] , Gooseberry anthocyanins [268] , Naringenin (NIN) [198] , Germacrone [269] , Brevilin A [270] , Curdione [271] , Limonin [272] , Piperlongumine [273] , Conophylline [274] , Apigenin [227] , Sal-B [219] , Taxifolin [275] , Vanillin [275] , Pterostilbene [276] , Sesamol [277] , Chelerythrine [278] , Physalin D [234] . (2) Reduced HSC activation by activating PPAR-g: Methoxyeugenol [226] , Apigenin [227] .…”
Section: Othersmentioning
confidence: 99%
“…Schisandrin C (Sch C), one of the lignans of Schisandra Chinese, has been shown to inhibit the TGF-β 1 /Smad2/3 signaling pathway which plays an important role in ECM deposition 4 , 23 . Thus, we hypothesized that Sch C might play a beneficial role in the diminishment of ECM deposition by inhibiting LOX expression contributing to ameliorating PF.…”
Section: Introductionmentioning
confidence: 99%